Stress, vibration, and wave analysis in aerospace composites : for SHM and NDE applications - Giurgiutiu, Victor (Academic Press, an imprint of Elsevier, 2022)
Stress, Vibration, and Wave Analysis in Aerospace Composites: SHM and NDE Applications presents a unified approach to studying and understanding stress, vibrations and waves in composite materials used in aerospace applications. --